PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSET, DAN CURRENT RATIO TERHADAP FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Sub Sektor Properti dan Real Estate Yang Terdaftar di BEI) - Aini, Siti Nur; Ferranti, Putri Andari (Journal of Fundamental Management (JFM), 2024)
This study aims to determine the effect of leverage ratio (Debt to Equity Ratio), profitability (Return on assets), and liquidity (Current Ratio) on financial distress in the property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX). The method of analysis used is descriptive analysis, panel data regression analysis, classical assumption test and hypothesis test that is processed using Eviews12. The sample used was 175 samples from 35 property and real estate sub-sector companies listed on the Indonesia Stock Exchange in the 2018-2022 period. The sample method uses purposive sampling method. The results of this study indicate that leverage (Debt to Equity Ratio) has a significant negative effect on financial distress, profitability (Return on Asset) and Liquidity (Current Ratio) has a significant positive effect on financial distress.